2012
DOI: 10.1111/j.1553-2712.2012.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Atropine Versus Metoclopramide: Can We Reduce Ketamine‐associated Vomiting in Young Children? A Prospective, Randomized, Open, Controlled Study

Abstract: In this study, a high rate (28.4%) of KAV was observed, consistent with prior reports using the intramuscular (IM) route. However, the authors were unable to reduce KAV using adjunctive atropine or metoclopramide. Parents or caregivers should be given more detailed discharge instructions about vomiting and diet considering the relatively long time to resuming a normal diet after ketamine sedation and the fact that KAV often occurred after ED discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
(56 reference statements)
1
22
2
Order By: Relevance
“…Previous studies have reported that the rate of emesis following ketamine sedation in paediatric patients varied widely, ranging between 6% and 28%. (14)(15)(16)(17) However, some of these studies included any emesis that occurred up to 24 hours after discharge from hospital. In the present study, emesis was defined as having at least one episode of vomiting occurring before discharge from the ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that the rate of emesis following ketamine sedation in paediatric patients varied widely, ranging between 6% and 28%. (14)(15)(16)(17) However, some of these studies included any emesis that occurred up to 24 hours after discharge from hospital. In the present study, emesis was defined as having at least one episode of vomiting occurring before discharge from the ED.…”
Section: Discussionmentioning
confidence: 99%
“…(14) This was also the first study that aimed to identify the risk factors of emesis in children undergoing IM ketamine sedation in our diverse local population. Previous studies have reported that the rate of emesis following ketamine sedation in paediatric patients varied widely, ranging between 6% and 28%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, while data are variable [131,136], the best (and most recent) prospective trial evidence suggests it is worthwhile to coadminister an antisialagogue such as atropine [123]. Third, although postketamine vomiting usually occurs well after ED discharge (and thus well after there is significant risk for aspiration), the occurrence of this "nuisance" side effect may be reduced by postprocedure utilization of an antiemetic such as ondansetron at home (atropine and metoclopramide do not appear to work well for this indication) [137].…”
Section: Ketaminementioning
confidence: 99%